Formation and propagation of pulsed high current plasma and ion beams in transverse magnetic field and magnetized plasma: autoreferat submitted for the scientific degree of Candidate of Physics and Mathematical Sciences; спец. 01.04.20 - Anderson M. G. Michael Gordon (Tomsk, [Б. и.], 2006)
Protection takes place 19.02.2006.